METHODOLOGICAL ASPECTS OF THE COURSE «SELF-IDENTITY AND SELF-REGULATION» IN SOCIAL SPHERE SPECIALISTS’ TRAINING - Tykholoz, V. (Вісник Черкаського національного університету імені Богдана Хмельницького. Серія: "Педагогічні науки", 2017)
Introduction. An important task of our time is the personality formation, capable for self-development, self-knowledge, self-understanding through his own nature and role realization in a dynamic world. Purpose. The purpose of the article is to highlight features of teaching «Self-identity and Self-regulation» in social sphere specialists’ training. Results. The goals and tasks of the course are defined, which are aimed at student’s disclosing the internal potential, his attitude to himself through self-knowledge, at becoming acquainted with the history, theory and methodology of self-education, at mastering self and life creation technologies, methods, techniques and skills of self-education activities. The article deals with the author’s approach to the study of the outstanding teachers’ contribution to the home history, theory and practice of self-identity and self-development based on primary sources investigation (Yaroslav the Wise, Vladimir Monomakh, Metropolitan Hilarion, Feofan Prokopovich, Hryhoriy Skovoroda, Taras Shevchenko, Lesya Ukrainka, M. Pirogov, I. Franko, K. Ushinsky, G. Vashchenko, Alexander Makarenko, V. Sukhomlinsky et al.). The specificity of the training course is singled out: 1) it is not so much educational as training course that promotes sustainable cultivation needs, the ability of the individual to self-education, self-development of itself; 2) the content of lessons is aimed at enabling role self-education awareness that will form the core of the ability to learn throughout life; 3) performing independent work and creative tasks, programming and self-educating, their own life project encourages students to choose and implement the methods of self-knowledge and self-education. The importance of methods and techniques of self-knowledge is determined: accumulating other people’s opinions of themselves, introspection, self-analysis, self-report, comparing yourself with others, verbalization of their own feelings and experiences, the use of special assistance. The basic forms and methods of work in preparing the course are offered: organizing discussions, trainings, business and creative games, contests, tests, diagnostic methods, presentations of books and creative works, meetings with creative people. The importance of developing plans and programs of self-education, mastering the technology of self-education influence is suggested. The motives of students’ self-education and self-development is found out as the future professional work and personal life. It is proved that the role of the teacher in the elaboration of the course is to develop self-conscious needs, creating favorable conditions for successful cultivation, collective self students. Discovered principles self-education of students: principles of development initiative and self-government. Conclusion. Now the role of social, psychological and personal factors and the human capacity for self-development, self-control and self-improvement, implementation of the educational process of the University mentioned in the article course is very important. We see the prospects for further research in the study of students’ readiness to self-educative activities. Experience of our work convinced that mastering the methods and techniques of self-educative activities in general, promotes active creative personality of the student.